2021
DOI: 10.3390/s21124035
|View full text |Cite
|
Sign up to set email alerts
|

Graph Representation Integrating Signals for Emotion Recognition and Analysis

Abstract: Data reusability is an important feature of current research, just in every field of science. Modern research in Affective Computing, often rely on datasets containing experiments-originated data such as biosignals, video clips, or images. Moreover, conducting experiments with a vast number of participants to build datasets for Affective Computing research is time-consuming and expensive. Therefore, it is extremely important to provide solutions allowing one to (re)use data from a variety of sources, which usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Comparative analysis showed that conventional EDA features can detect changes but have limitations in characterizing nuanced emotional states. In contrast, graph features demonstrated greater sensitivity to subtle state variations, aligning with evidence on complementarity of physiological signals and network representations [103]. Overall, this pioneering study introduced an EDA-graph framework that captures complex nonlinear emotion-signal relationships and enables granular state differentiation.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Comparative analysis showed that conventional EDA features can detect changes but have limitations in characterizing nuanced emotional states. In contrast, graph features demonstrated greater sensitivity to subtle state variations, aligning with evidence on complementarity of physiological signals and network representations [103]. Overall, this pioneering study introduced an EDA-graph framework that captures complex nonlinear emotion-signal relationships and enables granular state differentiation.…”
Section: Discussionmentioning
confidence: 53%
“…The suitability of GSP for processing EDA signals was suggested by previous studies that showed that graph representations better characterize discrete structural patterns rather than just amplitude differences [77], [103]. In particular, three features capturing node-level information, TLC and THC, and three features capturing graph-level information, GNC, Diameter, and Radius, exhibited significant differences between the five emotional states.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The distinction of a time series is based on the distinction used in [14] and [85]. In Figure 6, the two independent divisions are presented.…”
Section: ) Domain Descriptionmentioning
confidence: 99%